Supporting hemodynamics: what should we target? What treatments should we use? - Gattinoni, Luciano (BioMed Central, 2013)
Assessment and monitoring of hemodynamics is a cornerstone in critically ill patients as hemodynamic alteration may become life-threatening in a few minutes. Defining normal values in critically ill patients is not easy, because 'normality' is usually referred to healthy subjects at rest. Defining 'adequate' hemodynamics is easier, which embeds whatever pressure and flow set is sufficient to maintain the aerobic metabolism. We will refer to the unifying hypothesis proposed by Schrier several years ago. Accordingly, the alteration of three independent variables - heart (contractility and rate), vascular tone and intravascular volume - may lead to underfilling of the arterial tree, associated with reduced (as during myocardial infarction or hemorrhage) or expanded (sepsis or cirrhosis) plasma volume. The underfilling is sensed by the arterial baroreceptors, which activate primarily the sympathetic nervous system and renin-angiotensin-aldosterone system, as well as vasopressin, to restore the arterial filling by increasing the vascular tone and retaining sodium and water. Under 'normal' conditions, therefore, the homeostatic system is not activated and water/sodium excretion, heart rate and oxygen extraction are in the range found in normal subjects. When arterial underfilling occurs, the mechanisms are activated (sodium and water retention) - associated with low central venous oxygen saturation (ScvO(2)) if underfilling is caused by low flow/hypovolemia, or with normal/high ScvO(2 )if associated with high flow/hypervolemia. Although the correction of hemodynamics should be towards the correction of the independent determinants, the usual therapy performed is volume infusion. An accepted target is ScvO(2 )>70%, although this ignores the arterial underfilling associated with volume expansion/high flow. For large-volume resuscitation the worst solution is normal saline solution (chloride load, strong ion difference = 0, acidosis). To avoid changes in acid-base equilibrium the strong ion difference of the infused solution should be equal to the baseline bicarbonate concentration.